2012
DOI: 10.1186/1471-2458-12-877
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of governance of evolving response to non-communicable diseases in low-and middle- income countries: current status, risks and options

Abstract: BackgroundSegmented service delivery with consequent inefficiencies in health systems was one of the main concerns raised during scaling up of disease-specific programs in the last two decades. The organized response to NCD is in infancy in most LMICs with little evidence on how the response is evolving in terms of institutional arrangements and policy development processes.MethodsDrawing on qualitative review of policy and program documents from five LMICs and data from global key-informant surveys conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…There has been a substantial increase in the number of countries developing NCD‐specific policies since the early 2000s, most likely due to the World Health Assembly (WHA) endorsement of a global strategy on NCDs (Rani et al. ). A similar case can be made for the ‘helmet law’ from Viet Nam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a substantial increase in the number of countries developing NCD‐specific policies since the early 2000s, most likely due to the World Health Assembly (WHA) endorsement of a global strategy on NCDs (Rani et al. ). A similar case can be made for the ‘helmet law’ from Viet Nam.…”
Section: Resultsmentioning
confidence: 99%
“…In Cambodia and Fiji, the chair of the committee was the Minister of Health, and in Mongolia and Malaysia, the Prime Minister and Deputy Prime Minister, respectively (Rani et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes related to health systems performance were reported for several studies. This included the incorporation of research findings into national-level policy and strategy documents [46], the creation of new state agencies or units [50,51,70,79,80], and agenda-setting for the policy process [40,66]. The utilisation of knowledge to improve financial protection was illustrated in research from Mexico, which resulted in a reduction in out-ofpocket expenditure [44], and research from Colombia that noted a decline in spending for oncological treatment by users [77].…”
Section: Health System Outcomes and Health Impactsmentioning
confidence: 99%
“…Additionally, multple articles reflected on the use of research and routine system information to improve access to essential medicines and other pharmaceuticals [50,53,61,68,69,77,82]. Finally, knowledge utilisation was understood to enhance the quality of service delivery in research on integrated community case management in Malawi [64], non-communicable disease service delivery in five Asian countries [80], multiple primary care services in Nigeria [41], and male circumcision for HIV prevention in Uganda [45]. In this way, the review identified numerous studies that could loosely be characterised as corresponding to health system improvements.…”
Section: Health System Outcomes and Health Impactsmentioning
confidence: 99%
“…This includes governance reforms within the health portfolio, as well as inter-sectoral reforms that take account of the interests of different ministries and create the capacity for a government-wide response [39,40,133]. …”
Section: Establishing a National Legislative And Governance Frameworkmentioning
confidence: 99%